P.070 Thrombolysis without large vessel occlusion in a child with acute arterial ischemic stroke. (June 2019) - Hanes, IE; Orr, SL; Davila, J; Kirton, A; Sell, E
Abstract : Background: Stroke is a rare neurological disease in children, with an annual incidence of 2 - 13/100, 000 children per year. Pediatric stroke is associated with significant morbidity and mortality lasting many decades. Diagnosis of pediatric stroke is challenging and often delayed, limiting options for acute intervention, and the pharmacological and mechanical recanalization strategies that have revolutionized adult stroke remain undefined in children. Clinicians are left to draw conclusions from other retrospective cohort studies or case reports and extrapolate adult guidelines to the pediatric population. The TIPS trial eligibility criteria are often used in clinical practice, despite not being validated for this purpose. We present here the case of a healthy 14 year old male who was treated with intravenous tissue plasminogen activator (IV tPA) for a presumed arterial ischemic stroke without large vessel occlusion on neuroimaging. Methods: Retrospective chart review Results: Not applicable Conclusions: Following the administration of IV tPA, the patient made a full recovery. While we do not recommend the routine use of IV tPA for treatment of presumed large vessel or small vessel in children, we suggest that the decision to proceed with IV tPA be considered on a case-by-case basis.